2015
DOI: 10.17943/etku.78815
|View full text |Cite
|
Sign up to set email alerts
|

Bi̇li̇şi̇m Teknoloji̇leri̇ Öğretmenleri̇ni̇n Di̇nami̇k Web Teknoloji̇leri̇ni̇ Eği̇ti̇mde Kullanmalarina Yöneli̇k Görüşleri̇*

Abstract: Bilgi ve iletişim çağı olarak adlandırılan 21.yüzyılda teknolojide meydana gelen hızlı değişimler sonucunda; araştıran, sorgulayan, bilgiyi yeniden yapılandırabilen, yaratıcı düşünme, yansıtıcı düşünme, karar verme, eleştirel düşünme gibi üst düzey düşünme becerilerine sahip, girişimci ve işbirliği içinde çalışabilen nitelikli bireyler yetiştirmek toplumlar için önemli bir ihtiyaç haline gelmiştir. Bu ihtiyaç, yeni teknolojik bilgi ve deneyimlerin eğitime entegre edilmesi gerekliliğini de beraberinde getirmişt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Timur et al (2020) states that some teachers actively use social media applications as web 2.0 tools during their university education and benefit from these tools when they start their professional life, while some teachers have the opportunity to use different applications thanks to the web 2.0 tool lessons they took from the university. Horzum (2010) and Timur et al (2020) concluded that teachers; Kıyıcı (2010), Baltacı Göktalay and Özdilek (2010), Korucu and Çakır (2014) concluded that pre-service teachers actively use social networking, video sharing, and instant messaging sites. Çelik (2020) concluded that the applications that pre-service teachers can learn and integrate into the social studies course are Quizizz, Powtoon, Powerpoint, Mowi maker, Google Classroom, Toondoo, Classdojo, Canva and Flipquiz.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Timur et al (2020) states that some teachers actively use social media applications as web 2.0 tools during their university education and benefit from these tools when they start their professional life, while some teachers have the opportunity to use different applications thanks to the web 2.0 tool lessons they took from the university. Horzum (2010) and Timur et al (2020) concluded that teachers; Kıyıcı (2010), Baltacı Göktalay and Özdilek (2010), Korucu and Çakır (2014) concluded that pre-service teachers actively use social networking, video sharing, and instant messaging sites. Çelik (2020) concluded that the applications that pre-service teachers can learn and integrate into the social studies course are Quizizz, Powtoon, Powerpoint, Mowi maker, Google Classroom, Toondoo, Classdojo, Canva and Flipquiz.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Pre-service teachers emphasized about effects of using web 2.0 tools in social studies lessons on teachers that making it easier for teachers, supporting oral expression, being economical compared to other materials, demonstrating efficient use of technology to students, and teachers' self-development in the digital field, teachers discovering new applications in the web 2.0 tool design process, being able to be used as an evaluation tool, the necessity for teachers to have technological opportunities. Korucu and Yücel (2015) stated that web 2.0 tools have important effects such as increasing permanent learning, making the education process more effective, facilitating concept teaching, and increasing efficiency in education and training. While Özer and Albayrak Özer (2017) stated that preservice teachers think that the use of web 2.0 applications will save time and facilitate the education process, Efe (2014), Fırat, andKöksal (2017) have concluded that pre-service teachers' tendencies towards the use of web 2.0 tools in education are weak.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Öğretmenlere göre bu araçlar kullanıldığında soyut kavramlar daha somut hâle gelmekte ve öğrenme kolaylaşmaktadır. Korucu ve Yücel (2015), Web 2.0 araçlarının öğrenme ortamlarında katılımı arttırması, iş birliği sağlaması, kavram öğretimini daha somut hâle getirmesi, kalıcı ve etkin bir öğretim sağlaması, öğrenmeye teşvik etmesi gibi bir çok olumlu katkısına işaret etmiştir. Tekinarslan (2008), benzer katkılardan bahsetmiş ve bu katkıları nedeniyle Web 2.0 araçlarının eğitime entegrasyonunun önemine dikkat çekmiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Web 2.0 tools are also used in education due to their interactive features. Those features help students to acquire positive skills that enable meaningful learning, permanent learning, problem solving skills, critical thinking and working cooperatively (Korucu & Yücel, 2015).…”
Section: Introductionmentioning
confidence: 99%